2023
DOI: 10.1001/jamanetworkopen.2023.30961
|View full text |Cite
|
Sign up to set email alerts
|

Ki-67, 21-Gene Recurrence Score, Endocrine Resistance, and Survival in Patients With Breast Cancer

Janghee Lee,
Young-jin Lee,
Soong June Bae
et al.

Abstract: ImportanceBoth high 21-gene recurrence score (RS) and high Ki-67 level are poor prognostic factors in patients with estrogen receptor (ER)–positive ERBB2-negative (ER+/ERBB−) breast cancer; however, a discrepancy between the 2 has been noted. Survival differences according to these 2 biomarkers are not well known.ObjectiveTo assess the associations between RS and Ki-67 expression and between Ki-67 expression and recurrence-free survival in patients with ER+/ERBB− breast cancer with low RS.Design, Setting, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…We found, furthermore, that the proportion of Ki-67 levels was signi cantly higher for BC diagnosed outside the MSP. High Ki-67 levels are associated with higher grading and larger tumor size [18], and correlate to late endocrine resistance [19]. Consequently, we found that the number of mastectomies for cases within the MSP was about half compared to outside the MSP (8.9% vs 17.7%).…”
Section: Discussionmentioning
confidence: 89%
“…We found, furthermore, that the proportion of Ki-67 levels was signi cantly higher for BC diagnosed outside the MSP. High Ki-67 levels are associated with higher grading and larger tumor size [18], and correlate to late endocrine resistance [19]. Consequently, we found that the number of mastectomies for cases within the MSP was about half compared to outside the MSP (8.9% vs 17.7%).…”
Section: Discussionmentioning
confidence: 89%
“…We found, furthermore, that the proportion of Ki-67 levels is significantly higher for BC diagnosed outside the MSP. High Ki-67 levels are associated with higher grading, larger tumor size [ 19 ] and correlate to late endocrine resistance [ 20 ]. Consequently, we found that the number of mastectomies for cases within the MSP was about half compared to outside the MSP (8.9% vs. 17.7%).…”
Section: Discussionmentioning
confidence: 99%
“…We defined the values of estrogen receptor (ER) and progesterone receptor (PR) expression as positive or negative, and a cut-off value of 1% was set ( 30 ). A positive staining area ≤20% was defined as Ki-67 negative, while a positive staining area >20% was defined as Ki-67 positive ( 31 ). The histologic grade of the tumor tissue was assessed using the Bloom Richardson method.…”
Section: Methodsmentioning
confidence: 99%